PERAN GOOD CORPORATE GOVERNANCE DALAM MENEKAN MANAJEMEN LABA (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2008-2011) - Petrus Fraidylegif Putra Djatu; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
Earning management is considered harmful action to external side of companies. This action taking by manager to increase their own benefit. The mechanism of Good Coprporate governance are considerd can reduce earning management. This study aims to examine the role of Good Corporate Governance (GCG) in reducing earning management in manufacturing companies listed on Indonesia Stock Exchange (BEI) period of 2008-2011. Good Corporate Governance consist of intern governance and extern governance. Intern governance in this study consist of independent director, audit committee, and Risk Management Committee (RMC). Extern governance in this study is auditor big four. Earning management measured by Discretionary accruals, which is counted by kaznik model. This study use method of documentation for collecting data. Type of data in this study is secondary data. Secondary data is a financial statementswas issued by companies inIndonesia Stock Exchange (BEI). Financial statement data The method of anwas obtained from company financial statement which published by Indonesia Direct Exchange (IDX). The method of analysis was used in this study is multiple regression. This study uses data manufacturing company which listed in Indonesia Stock Exchange (BEI) in the year 2008 – 2011.Taking samples was usedproposive sampling technique. Number of samples taken in this study were 268. The result of this study showed that the variable has a negative and significant effect on earning management are independent directors, audit committee, and Risk Management Committee (RMC). Variable auditor big four had no effect on the low level of earning management.